(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Regional economic integration and regional cooperation can contribute significantly towards strengthening the three sets of factors the macroeconomic environment social policy, particularly in sectors related to human development, such as education, health and nutrition and the microenvironment that governs the empowerment of people and community participation that promote human development. Regional economic integration is both a process and a state of affairs. This paper is an attempt to try to discuss the regional economic, political etc. prospective of Asian region countries.The Regional Comprehensive Economic Partnership (RCEP ) was introduced during the 19th Asean meet held in November 2011. The RCEP negotiations were kick-started during the 21st Asean Summit in Cambodia in November 2012.In 2017, the 16 prospective signatories (including India) accounted for a population of 3.4 billion people with a total Gross Domestic Product (GDP) of 49.5 trillion, about half of the world population and 39 percent of the world’s GDP.The RCEP is a proposed free trade agreement in the Asia-Pacific region between the ten member states of the Association of South-East Asian Nations and their six FTA partners.